Metaphor in Funny Language - Asst. Instructor: Ayad Enad Khalaf (الأستاذ, 2018)
This article highlights different ways of metaphorical use in language and shows its potential in attracting the readers' attention. Language as a biological being lives its own life witnessing never-ending changes: falling outs and newly built elements. We enrich our language not only by new elements but also by new styles and reusing of existing sources. One of these ways which makes language more alive and active is metaphor. Metaphor nowadays is found in all the fields of life, education, medicine, policy and everyday life. Metaphor, in fact, reflects the relationship of language to culture and the world of ideas. Language, on the one hand, is a repository of culture; the traditions, proverbs, and knowledge of our ancestors. On the other hand, language is the mirror of the world of ideas. People reflect their new ideas in using language in new ways, even such devices as paintings and riddles. Metaphor has many shapes and is found in spoken and written language, graphics, cartoon or caricature, riddles, jokes and paintings to express novel shades of meanings, e.g., metaphor in newspaper photos, magazines or even in advertisements attracts the attention of readers and are memorized for a long time. Metaphoric use is also a way of enjoying the readers. It is used for both real and logical aims such as; warnings, advises, or invitations ...etc